Health effects of climate change: an overview of systematic reviews. Issue 6 (9th June 2021) - Rocque, Rhea J; Beaudoin, Caroline; Ndjaboue, Ruth; Cameron, Laura; Poirier-Bergeron, Louann; Poulin-Rheault, Rose-Alice; Fallon, Catherine; Tricco, Andrea C; Witteman, Holly O
Abstract : Objectives: We aimed to develop a systematic synthesis of systematic reviews of health impacts of climate change, by synthesising studies' characteristics, climate impacts, health outcomes and key findings. Design: We conducted an overview of systematic reviews of health impacts of climate change. We registered our review in PROSPERO (CRD42019145972). No ethical approval was required since we used secondary data. Additional data are not available. Data sources: On 22 June 2019, we searched Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, Cochrane and Web of Science. Eligibility criteria: We included systematic reviews that explored at least one health impact of climate change. Data extraction and synthesis: We organised systematic reviews according to their key characteristics, including geographical regions, year of publication and authors' affiliations. We mapped the climate effects and health outcomes being studied and synthesised major findings. We used a modified version of A MeaSurement Tool to Assess systematic Reviews-2 (AMSTAR-2) to assess the quality of studies. Results: We included 94 systematic reviews. Most were published after 2015 and approximately one-fifth contained meta-analyses. Reviews synthesised evidence about five categories of climate impacts; the two most common were meteorological and extreme weather events. Reviews covered 10 health outcome categories; the 3 most common were (1) infectious diseases, (2) mortality and (3) respiratory, cardiovascular or neurological outcomes. Most reviews suggested a deleterious impact of climate change on multiple adverse health outcomes, although the majority also called for more research. Conclusions: Most systematic reviews suggest that climate change is associated with worse human health. This study provides a comprehensive higher order summary of research on health impacts of climate change. Study limitations include possible missed relevant reviews, no meta-meta-analyses, and no assessment of overlap. Future research could explore the potential explanations between these associations to propose adaptation and mitigation strategies and could include broader sociopsychological health impacts of climate change.